Rhodium-catalyzed C–C coupling reactions via double C–H activation - Li, Shuai-Shuai; Qin, Liu; Dong, Lin (Organic & biomolecular chemistry, 2016)
Various rhodium-catalyzed double C–H activations are reviewed. These powerful strategies have been developed to construct C–C bonds, which might be widely embedded in complex aza-fused heterocycles, polycyclic skeletons and heterocyclic scaffolds. In particular, rhodium( iii ) catalysis shows good selectivity and reactivity to functionalize the C–H bond, generating reactive organometallic intermediates in most of the coupling reactions. Generally, intermolecular, intramolecular and multi-component coupling reactions via double C–H activations with or without heteroatom-assisted chelation are discussed in this review.